Exploring Antecedents: Key Factors Shaping Global Entrepreneurial Intention - Sulistyowati, Tussi; Sukati, Inda (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: Entrepreneurship involves more than just conceiving a viable idea; it necessitates fostering the right mindset for progress. Understanding the antecedents and crucial factors influencing global entrepreneurial intention is pivotal in shaping effective entrepreneurship policies and creating an enabling environment.Purpose: This research undertakes a thorough investigation into the antecedents and crucial factors influencing global entrepreneurial intention.Design/Methodology/Approach: Utilizing a robust qualitative method through a systematic literature review, the study meticulously scrutinized 772 papers from the Scopus database spanning 2015-2024, with a specific emphasis on entrepreneurial intentions. The deliberate selection of 31 articles underscored a systematic approach, enriching the dataset with the utmost relevance.Findings/Results: Across diverse economies like Saudi Arabia, India, China, and the United States, the study uncovered various research methodologies. Insights drawn from internal, external, and personal factors were examined through the lens of the Theory of Planned Behavior, shedding light on the complexities of entrepreneurial intentions. These findings, aligned with key concepts such as motivation, creativity, and self-efficacy, underscored the theory's applicability and deepened our understanding of the multifaceted dynamics shaping entrepreneurial intentions.Conclusion: The insights derived from this study should be considered when formulating entrepreneurship policies aimed at creating an enabling environment that addresses systemic barriers and fosters a culture of entrepreneurship.Originality/Value (State of the Art): This research offers a comprehensive and systematic exploration of the factors influencing entrepreneurial intention globally, employing a qualitative method and systematic literature review. It contributes significantly to the existing body of knowledge by contextualizing the Theory of Planned Behavior within diverse economic settings, thereby enhancing our understanding of the intricate dynamics that influence entrepreneurial intentions. Keywords: antecedent, entrepreneurial intention, Scopus, systematic literature review, Theory of Planned Behavior (TPB)